Green fiscal reform for a just energy transition in Latin America - Michael Jakob; Rafael Soria; Carlos Trinidad; Ottmar Edenhofer; Céline Bak; Daniel Bouille; Daniel Buira; Hernan Carlino; Veronica Gutman; Christian Hübner; Brigitte Knopf; André Lucena; et al. (Economics: The Open-Access, Open-Assessment E-Journal, 2019)
Green fiscal reforms would contribute to climate change mitigation, increase the economic efficiency of national tax systems and provide additional public revenues. Some countries in Latin America have already taken first steps towards green fiscal reforms. This outlook article provides an overview of the major challenges for the successful implementation of such reforms and discusses how they could be overcome.
Keywords: H23; E62; Q54; N16; Q48; 330; green fiscal reform; energy subsidies; Latin America; multi-objective climate policy; sequencing; distribution